A near-infrared fluorescent probe based on a hemicyanine dye with an oxazolidine switch for mitochondrial pH detection. Issue 3 (23rd December 2020) - Mazi, Wafa; Yan, Yunnan; Zhang, Yibin; Xia, Shuai; Wan, Shulin; Tajiri, Momoko; Luck, Rudy L.; Liu, Haiying
Abstract : A near-infrared fluorescent probe (AH+ ) has been prepared by incorporating an oxazolidine switch into a near-infrared hemicyanine dye for pH detection in the mitochondria of HeLa cells. Abstract : A near-infrared fluorescent probe (AH+ ) has been prepared by incorporating an oxazolidine switch into a near-infrared hemicyanine dye. The probe shows fast and sensitive responses to pH from an oxazolidine switch to the hemicyanine dye upon pH decreases from 10.0 to 5.0. The probe shows good photostability, low cytotoxicity, and reversible fluorescence responses to pH changes with a p K a value of 7.6. It has been successfully used to determine pH changes in mitochondria.